Schedule instability in a supply chain: an experimental study. Issue 1 (3rd July 2008) - Pujawan, I. Nyoman
This study investigates how different supply chain policies and different operating environments affect schedule instability in a supply chain. Experimental study on a simple supply chain system consisting of a buyer and a supplier is conducted. The results suggest that schedule instability is propagated up the supply chain and is much affected by the degree of demand uncertainty from the end customers. It is also shown that safety stock policy applied by the buyer has much impact on schedule instability experienced by the supplier, but such an impact is affected by the degree of demand uncertainty.